Effect of artificial short-days on morphological characterization of standard chrysanthemum (Chrysanthemum morifolium Ramat) genotypes - RANJIT SINGH; DHAWAN SHWETA MACCHINDRA; MADHU BALA (Journal of Ornamental Horticulture, 2024)
The present investigation was conducted at the Research Farm, Department of Floriculture and Landscaping, Punjab Agricultural University, Ludhiana, from 2018 to 2019. The plants were propagated through the rooted terminal cuttings between February and March, and they underwent short-day treatment, involving the use of a black polythene sheet (100 microns thick) to extend the night period from civil twilight in the morning until 9 O’clock. The results revealed that ’Snow Ball’ exhibited the tallest plant height (99.47 and 99.46 cm), while ’Yellow Star’ and ’Casa Grande’ had the largest stem diameter (6.56 and 6.76 mm). ’Kikibiory’ showed the highest partitioning coefficient (24.91 and 24.90) in both years. However, parameters such as leaf area index, leaf weight ratio, and stomata count per unit area were not significantly affected. ’Denise Oatridge’ had the shortest time to flower bud appearance (164.99 and 164.92 days), resulting in early flowering (189.29 and 189.22 days), and ’Snow Ball’ exhibited the longest vase life (13.02 and 13.05 days).